S100A1 is a Potential Biomarker for Papillary Thyroid Carcinoma Diagnosis and Prognosis - Wang, Ge; Li, Han-ning; Cui, Xiao-qing; Xu, Tao; Dong, Meng-lu; Li, Shu-yu; Li, Xing-rui (Journal of Cancer, 2021)
S100 calcium binding protein A1 (S100A1) is an important member of the S100 family and known to express in a variety of cancers. However, the biological functions of S100A1 in thyroid carcinoma have not been thoroughly studied. In this report, bioinformatics analyses and immunohistochemistry assays were applied to assess the expression profile of S100A1 as well as its relationship with the pathological features and prognosis of papillary thyroid carcinoma (PTC). Meanwhile, functions of S100A1 in PTC cells were analyzed with either or experiments. S100A1 was significantly up-regulated in PTC tissues compared with adjacent non-cancerous tissues. S100A1 protein expression was significantly associated with tumor size ( =0.0032) or lymph node metastasis ( =0.0331). More importantly, an elevated S100A1 expression was significantly correlated with a worse recurrence-free survival (RFS) (HR=2.26, =0.042). Further, knockdown of S100A1 dramatically inhibited cell proliferation and migration as well as increased apoptosis of PTC cells. S100A1 knockdown inhibited tumor progression as seen in experiments. In terms of mechanism, down-regulation of S100A1 induced yes associated protein (YAP) phosphorylation in the cytoplasm and diminished Hippo/YAP pathway activation. Therefore, S100A1 may serve as a novel oncogene and a promising biomarker for PTC diagnosis and prognosis.